Rhizosphere - Rhizosphere (Elsevier, 2026)
Rhizosphere is a multidisciplinary journal that publishes research on the interactions between plant roots, soil organisms, nutrients, and water. Except carbon fixation by photosynthesis, plants obtain all other elements primarily from soil through roots. Rhizosphere aims to advance the frontier of our understanding of plant-soil interactions.
FI 1.03
Q1
Keywords: Earth; Space & Environmental Sciences; Atmospheric Sciences; Acuerdos transformativos; Transformative agreements; Rizosfera; Interacción planta-suelo; Microorganismos del suelo; Ecología del suelo